HDR prostate brachytherapy plan robustness and its effect on in‐vivo source tracking error thresholds: A multi‐institutional study. Issue 6 (19th April 2022) - Poder, Joel; Koprivec, Dylan; Dookie, Yashiv; Howie, Andrew; Cutajar, Dean; Damato, Antonio L.; Côté, Nicolas; Petasecca, Marco; Bucci, Joseph; Rosenfeld, Anatoly
Abstract: Purpose: The purpose of this study was to examine the effect of departmental planning techniques on appropriate in‐vivo source tracking error thresholds for high dose rate (HDR) prostate brachytherapy (BT) treatments, and to determine if a single in‐vivo source tracking error threshold would be appropriate for the same patient anatomy. Methods: The prostate, rectum, and urethra were contoured on a single patient transrectal ultrasound (TRUS) dataset. Anonymized DICOM files were disseminated to 16 departments who created an HDR prostate BT treatment plan on the dataset with a prescription dose of 15 Gy in a single fraction. Departments were asked to follow their own local treatment planning guidelines. Source positioning errors were then simulated in the 16 treatment plans and the effect on dose–volume histogram (DVH) indices calculated. Change in DVH indices were used to determine appropriate in‐vivo source tracking error thresholds. Plans were considered to require intervention if the following DVH conditions occurred: prostate V100% < 90%, urethra D0.1cc > 118%, and rectumtt D max > 80%. Results: There was wide variation in appropriate in‐vivo source tracking error thresholds among the 16 participating departments, ranging from 1 to 6 mm. Appropriate in‐vivo source tracking error thresholds were also found to depend on the direction of the source positioning error and the endpoint. A robustness parameter was derived, and found to correlate with the sensitivity of plans to source positioning errors. Conclusions: A single HDR prostate BT in‐vivo source tracking error threshold cannot be applied across multiple departments, even for the same patient anatomy. The burden on in‐vivo source tracking devices may be eased through improving HDR prostate BT plan robustness during the plan optimisation phase.